2021
DOI: 10.5713/ajas.20.0199
|View full text |Cite
|
Sign up to set email alerts
|

Performance of growing lambs supplemented with ground licuri (Syagrus coronata)

Abstract: The aim of this study was to determine the effect of dietary ground licuri on lamb performance. Methods: Forty male lambs were used in a completely randomized design to test the effects of 0, 5, 10, and 15 g/kg of ground licuri added to diets. The trial lasted for 75 days. Intake, digestibility, physically effective neutral detergent fiber (peNDF), and chewing activity were estimated. Blood samples were taken on day 45 to determine the concentrations of glucose, urea, non-esterified fatty acids (NEFA), and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
1
Order By: Relevance
“…We propose that despite being richer in NDIN and ADIN than soybean meal, the use of licuri provided a lower rate of passage of fermentable organic matter due to its higher NDF content, resulting in greater synthesis of rumen microbial protein. Daza et al (2020) also did not observe an effect of the inclusion of licuri nut on the apparent digestibility of CP in a sheep diet.…”
Section: Discussionmentioning
confidence: 68%
“…We propose that despite being richer in NDIN and ADIN than soybean meal, the use of licuri provided a lower rate of passage of fermentable organic matter due to its higher NDF content, resulting in greater synthesis of rumen microbial protein. Daza et al (2020) also did not observe an effect of the inclusion of licuri nut on the apparent digestibility of CP in a sheep diet.…”
Section: Discussionmentioning
confidence: 68%
“…Diets with higher NDF contents result in more chewing (see upward trend in chewing time) and, consequently, more saliva in the rumen-reticulum to regulate the pH of this compartment (Souza et al, 2022). In this context, Daza et al (2021) reported that the physically effective NDF (peNDF1.18) content of licuri is similar to that of Tifton 85 hay, and that including the former ingredient in the diet increases its peNDF level. Furthermore, for cows whose DM intake is regulated by the diet's energy density (i.e., in high-grain diets), increasing the dietary peNDF may favor DM intake (Zebeli et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The crude protein in LC is rich in neutral and acid detergent insoluble protein (Silva et al, 2015), and its ether extract is rich in short-and medium-chain fatty acids (Costa et al, 2018). Additionally, the neutral detergent fiber in LC is as effective as that of hay (Daza et al, 2021). Researchers who replaced soybean meal (the main dietary source of protein) with LC in the diet of sheep described a decrease in nutrient intake and digestibility, performance, and carcass traits (Santos et al, 2015;Costa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of 17% ground licuri in the diet of lambs improved feed conversion and increased average daily gain [239]. However, a decrease in lamb performance due to decreased dry matter intake was observed [240]. The lambs fed with 16% licuri cake had no changes in the dry matter intake [241].…”
Section: Macaúba Kernelmentioning
confidence: 97%